Adaptation strategies of endolithic chlorophototrophs to survive the hyperarid and extreme solar radiation environment of the Atacama Desert - Wierzchos, Jacek; DiRuggiero, Jocelyne; Vítek, Petr; Artieda, Octavio; Souza-Egipsy, Virginia; Skaloud, Pavel; Tisza, Michael; Davila, Alfonso F.; Vílchez, Carlos; Garbayo, Inés; Ascaso, Carmen (Frontiers in Microbiology, 2015)
The Atacama Desert, northern Chile, is one of the driest deserts on Earth and, as such, a natural laboratory to explore the limits of life and the strategies evolved by microorganisms to adapt to extreme environments. Here we report the exceptional adaptation strategies of chlorophototrophic and eukaryotic algae, and chlorophototrophic and prokaryotic cyanobacteria to the hyperarid and extremely high solar radiation conditions occurring in this desert. Our approach combined several microscopy techniques, spectroscopic analytical methods, and molecular analyses. We found that the major adaptation strategy was to avoid the extreme environmental conditions by colonizing cryptoendolithic, as well as, hypoendolithic habitats within gypsum deposits. The cryptoendolithic colonization occurred a few millimeters beneath the gypsum surface and showed a succession of organized horizons of algae and cyanobacteria, which has never been reported for endolithic microbial communities. The presence of cyanobacteria beneath the algal layer, in close contact with sepiolite inclusions, and their hypoendolithic colonization suggest that occasional liquid water might persist within these sub-microhabitats. We also identified the presence of abundant carotenoids in the upper cryptoendolithic algal habitat and scytonemin in the cyanobacteria hypoendolithic habitat. This study illustrates that successful lithobiontic microbial colonization at the limit for microbial life is the result of a combination of adaptive strategies to avoid excess solar irradiance and extreme evapotranspiration rates, taking advantage of the complex structural and mineralogical characteristics of gypsum deposits – conceptually called “rock’s habitable architecture”. Additionally self-protection by synthesis and accumulation of secondary metabolites likely produces a shielding effect that prevents photoinhibition and lethal photooxidative damage to the chlorophototrophs, representing another level of adaptation.